2019
DOI: 10.1002/jbmr.3662
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epigenomics in Bone and Cartilage Disease

Abstract: Phenotypic variation in skeletal traits and diseases is the product of genetic and environmental factors. Epigenetic mechanisms include information-containing factors, other than DNA sequence, that cause stable changes in gene expression and are maintained during cell divisions. They represent a link between environmental influences, genome features, and the resulting phenotype. The main epigenetic factors are DNA methylation, posttranslational changes of histones, and higher-order chromatin structure. Sometim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 184 publications
(290 reference statements)
2
44
0
2
Order By: Relevance
“…Due to mice small size, a 0.8 mm diameter flat-tipped cylindrical punch was fixed to the actuator of the materials testing machine and compressed directly to record the mechanical properties data. Uma Sankar and many studies developed and improved this method to measure the axial compressive strength of the cancellous bone in femur of mice, which is more precise and visual than finite element modeling [38][39][40][41][42][43]. The present result in Sham group was consistent with form studies.…”
Section: Declined Trabecular Bone Mineralization In Dm-oa Groupsupporting
confidence: 84%
“…Due to mice small size, a 0.8 mm diameter flat-tipped cylindrical punch was fixed to the actuator of the materials testing machine and compressed directly to record the mechanical properties data. Uma Sankar and many studies developed and improved this method to measure the axial compressive strength of the cancellous bone in femur of mice, which is more precise and visual than finite element modeling [38][39][40][41][42][43]. The present result in Sham group was consistent with form studies.…”
Section: Declined Trabecular Bone Mineralization In Dm-oa Groupsupporting
confidence: 84%
“…Epigenetic modifications in bone cells affect the development and therapeutic sensitivity of osteoporosis [35]. An MSC transplantation study showed that MSC-derived exosomes transfer FAS to BMMSCs of recipient FAS-mutated MRL/lpr mice to modify the DNA methylation status of Notch, bone volume in OVX mice.…”
Section: Discussionmentioning
confidence: 99%
“…SHED-EVs also rescued the impaired function of recipient BMMSCs by regulating Tert-associated telomerase activity. Thus, SHED-EVs appear to play a crucial role in the biological crosstalk between donor SHED and recipient BMMSCs to achieve therapeutic effects in postmenopausal osteoporosis.Epigenetic modifications in bone cells affect the development and therapeutic sensitivity of osteoporosis [35]. An MSC transplantation study showed that MSC-derived exosomes transfer FAS to BMMSCs of recipient FAS-mutated MRL/lpr mice to modify the DNA methylation status of Notch, bone volume in OVX mice.…”
mentioning
confidence: 99%
“…Epigenetic modi cations in bone cells affect the development and therapeutic sensitivity of osteoporosis [47]. An MSC transplantation study show that MSC-derived exosomes transfer FAS to BMMSCs of recipient FAS-mutated MRL/lpr mice to modify the DNA methylation status of Notch, resulting in the rescue of impaired recipient BMMSC function [15].…”
Section: Discussionmentioning
confidence: 99%